Antibiotic Resistance and Presence of Persister Cells in the Biofilm-like Environments in Streptococcus agalactiae - Pamella Silva Lannes-Costa; Isabelle Rodrigues Fernandes; João Matheus Sobral Pena; Brunno Renato Farias Verçoza Costa; Marcel Menezes Lyra da Cunha; Bernadete Teixeira Ferreira-Carvalho; Prescilla Emy Nagao (MDPI AG, 2024)
Objectives: This study investigated antibiotic resistance and presence of persister cells in Streptococcus agalactiae strains belonging to capsular types Ia/ST-103, III/ST-17, and V/ST-26 in biofilm-like environments. Results: S. agalactiae strains were susceptible to penicillin, clindamycin, and erythromycin. Resistance genes were associated with tetM (80%), tetO (20%), ermB (80%), and linB (40%). Persister cells were detected in bacterial strains exposed to high concentrations of penicillin, clindamycin, and erythromycin. S. agalactiae capsular type III/ST-17 exhibited the highest percentage of persister cells in response to penicillin and clindamycin, while type Ia/ST-103 presented the lowest percentages of persister cells for all antimicrobials tested. Additionally, persister cells were also detected at lower levels for erythromycin, regardless of capsular type or sequence type. Further, all S. agalactiae isolates presented efflux pump activity in ethidium bromide-refractory cell assays. LIVE/DEAD fluorescence microscopy confirmed the presence of >85% viable persister cells after antibiotic treatment. Conclusions: These findings suggest that persister cells play a key role in the persistence of S. agalactiae during antibiotic therapy, interfering with the treatment of invasive infections. Monitoring persister formation is crucial for developing strategies to combat recurrent infections caused by this pathogen.